2017
DOI: 10.1007/s00256-017-2763-x
|View full text |Cite
|
Sign up to set email alerts
|

Osseous spurs at the fovea capitis femoris—a frequent finding in asymptomatic volunteers

Abstract: Smaller osseous spurs (<2 mm) at the border of the fovea capitis femoris are very common in asymptomatic volunteers and do not seem to be pathologic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Some studies evaluating FCF dimensions have measured the largest diameter of the FCF (TL-FCF) in axial and coronal sections on computed tomography or magnetic resonance images (MRI) [11,12,16]. In asymptomatic volunteers, the width of FCF found by Bensler et al did not contain similar results to our ndings.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some studies evaluating FCF dimensions have measured the largest diameter of the FCF (TL-FCF) in axial and coronal sections on computed tomography or magnetic resonance images (MRI) [11,12,16]. In asymptomatic volunteers, the width of FCF found by Bensler et al did not contain similar results to our ndings.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, an excess of nutrient foramina reduces the likelihood of developing osteonecrosis [6]. Hip dysplasia and osteoarthrosis have been related to modi cations in the morphometric structure and location of the FCF in the hip joint [10][11][12]. As the femoral head is supplied by vessels that travel through the FCF, the features of the anatomical structures on the head of the femur are considered potential factors in avascular necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric and morphological characteristics of the FLHOF are essential for the surgical approaches for preservation or reconstruction of the injured LHOF due to its relationship with this ligament (1,2). It has been reported that the relationship between the morphometry of the FLHOF and its position with the development of dysplasia and osteoarthritis in the hip joint (3,4). Morphological features of FLHOF may provide useful information in clinical practice for objective evaluation of DOI: 10.37990/medr.1107706 the hip joint osteoarthritis and LHOF.…”
Section: Introductionmentioning
confidence: 99%
“…2 ): labrum damage > 2 h on the clockface (labral base tear, tear within labrum substance, complex labrum tear), femoral cartilage damage (delamination, thinning, defect), ligamentum teres damage (tear/ hypertrophy) [ 18 ], acetabular rim cyst, peripheral-/ central “perifoveolar” femoral osteophytes, and peripheral acetabular/ central “acetabular fossa” osteophytes [ 10 , 19 ]. The presence of a central femoral osteophyte was defined as > 2 mm [ 19 ]. No size cutoff was used for the remaining osteophytes due to the lack of established criteria.…”
Section: Methodsmentioning
confidence: 99%